2021
DOI: 10.1038/s41467-021-24240-3
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous MTAP deletion in primary human glioblastoma is not associated with elevation of methylthioadenosine

Abstract: Homozygous deletion of methylthioadenosine phosphorylase (MTAP) in cancers such as glioblastoma represents a potentially targetable vulnerability. Homozygous MTAP-deleted cell lines in culture show elevation of MTAP’s substrate metabolite, methylthioadenosine (MTA). High levels of MTA inhibit protein arginine methyltransferase 5 (PRMT5), which sensitizes MTAP-deleted cells to PRMT5 and methionine adenosyltransferase 2A (MAT2A) inhibition. While this concept has been extensively corroborated in vitro, the clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
1
23
2
Order By: Relevance
“…We suspect that the excretion of MTA is largely a passive event, such that if extracellular MTA is low the MTAP-cell can reduce its intracellular MTA by dilution. This finding is entirely consistent with the recent observation that in MTAP-deleted human glioblastoma tumor tissue there is no increase in MTA (27), raising the idea that the amount of MTAP+ stromal cells may be an important factor when trying to target MTAP-loss therapeutically via PRMT5 inhibition. Smith and colleagues have recently J o u r n a l P r e -p r o o f developed a small molecule PRMT5 inhibitor that specifically targets the PRMT5-MTA complex (28).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We suspect that the excretion of MTA is largely a passive event, such that if extracellular MTA is low the MTAP-cell can reduce its intracellular MTA by dilution. This finding is entirely consistent with the recent observation that in MTAP-deleted human glioblastoma tumor tissue there is no increase in MTA (27), raising the idea that the amount of MTAP+ stromal cells may be an important factor when trying to target MTAP-loss therapeutically via PRMT5 inhibition. Smith and colleagues have recently J o u r n a l P r e -p r o o f developed a small molecule PRMT5 inhibitor that specifically targets the PRMT5-MTA complex (28).…”
Section: Discussionsupporting
confidence: 90%
“…However, our findings and those of Barekatain et al. ( 27 ) suggest that in vivo there may be no elevation in intracellular MTA because of its being metabolized by MTAP+ stromal cells. Additional studies will need to be performed to see how universal is this phenomenon.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In a similar manner, others have considered the potential role of the tumor microenvironment in therapy directed against MTAP-deficient cells [59]. Glioblastoma tumors are heterogenous, containing distinct tumor cell types as well as normal cells including neurons, astrocytes, microglia, macrophages, neutrophils, lymphocytes, and endothelial cells.…”
Section: Methionine and Polyamine Synthesismentioning
confidence: 99%
“…At the same time, high MTA concentrations reduce the sensitivity of cells to arginine-N-methyltransferase, which can be used for antitumor therapy. When using the physiological Plasmax medium, Barekatain et al [ 48 ] showed that the above-described mutation does not cause the accumulation of MTA in cells but promotes its secretion. Moreover, secreted MTA can be absorbed by stromal cells in vivo , which has been demonstrated in the co-culture experiment with glioblastoma cells and macrophages.…”
Section: Application Of Plasma-like Media In Biomedical Researchmentioning
confidence: 99%